Introduced mammals of the world : their history, distribution, and influence - Long, John L. (CABI Pub. ; CSIRO Pub., 2003)
Introduced Mammals of the World provides a concise and extensive source of information on the range of introductions of mammals conducted by humans, and an indication as to which have resulted in adverse outcomes. It provides a very valuable tool by which scientists can assess future potential introductions (or re-introductions) to avoid costly mistakes.